MUSIC AND LANGUAGE IN INTERDISCIPLINARY CONNECTION - Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Nowadays speech and language development is actual problem. This research was conducted to find out how music could help in solving this problem and to find out how connected music and language processes are in our brain. Language and music share a lot of similarities in terms of neurology, Music Therapy, communication and psychology and their interactions are successfully used in these sciences. Aim of this research was to gather data and scientific basis for music’s ability to improve speech and language. Main findings indicate that this topic has been studied for decades and still hasn’t lost its significance. Music can influence language processes, lessen disorders because it is neurologically and psychologically close to our spoken language.